Recent progress on harm, pathogen classification, control and pathogenic molecular mechanism of anthracnose of oil-tea - Chen, Xinggang; Chen, Xingzhou; Tan, Qian; Mo, Xiuli; Liu, Junang; Zhou, Guoying (Frontiers in Microbiology, 2022)
Oil tea (Camellia oleifera), mainly used to produce high-quality edible oil, is an important cash crop in China. Anthracnose of oil tea is a considerable factor that limits the yield of tea oil. In order to effectively control the anthracnose of oil tea, researchers have worked hard for many years, and great progress has been made in the research of oil tea anthracnose. For instance, researchers isolated a variety of Colletotrichum spp. from oil tea and found that Colletotrichum fructicola was the most popular pathogen in oil tea. At the same time, a variety of control methods have been explored, such as cultivating resistant varieties, pesticides, and biological control, etc. Furthermore, the research on the molecular pathogenesis of Colletotrichum spp. has also made good progress, such as the elaboration of the transcription factors and effector functions of Colletotrichum spp. The authors summarized the research status of the harm, pathogen types, control, and pathogenic molecular mechanism of oil tea anthracnose in order to provide theoretical support and new technical means for the green prevention and control of oil tea anthracnose.